The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/int.22274
|View full text |Cite
|
Sign up to set email alerts
|

Garra Rufa‐inspired optimization technique

Abstract: Natural selection has inspired researchers to develop and apply several intelligent optimization techniques in the past few decades. Generally, in artificial intelligence optimization, the particles follow a local or global best particle until finding an acceptable solution. In well‐ developed optimization techniques, such as swarm optimization (PSO) and the firefly algorithm (FA), getting around the initial optimal value of the group and randomly checking the effect of the surrounding points may lead to a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The Garra Rufa fish optimization (GRFO) depends on Garra Rufa movements, the particles have been divided as groups, the better optimum value leads every group 35 . This is a new metaheuristic optimization approach depending on psychology of students who are annoying harder to improve its exam performance becoming the better student in class 36 …”
Section: Proposed Methodology Of Garra Rufa Fish Optimization (Grfo) ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Garra Rufa fish optimization (GRFO) depends on Garra Rufa movements, the particles have been divided as groups, the better optimum value leads every group 35 . This is a new metaheuristic optimization approach depending on psychology of students who are annoying harder to improve its exam performance becoming the better student in class 36 …”
Section: Proposed Methodology Of Garra Rufa Fish Optimization (Grfo) ...mentioning
confidence: 99%
“…35 This is a new metaheuristic optimization approach depending on psychology of students who are annoying harder to improve its exam performance becoming the better student in class. 36…”
Section: Proposed Methodology Of Garra Rufa Fish Optimization (Grfo) ...mentioning
confidence: 99%
“…Since the artificial intelligent applications started to have a real application, the intelligent control and optimization strategies are getting very fast development and modifications to be applied for all engineering, medicine, and economic challenges [35]- [40]. The intelligent systems improve the EVs operation and efficiency by several strategies, such as control the driver, optimizing the batteries, and develop a smart power system.…”
Section: Artifical Intelligant Techqniques In Evsmentioning
confidence: 99%
“…The study by Touma [5] proposed the whale optimization approach of finding a solution to the ED problem. The proposed system was evaluated in a standard IEEE 30-Bus testbed and the performance was compared with those of other optimization algorithms, such as elephant heart optimization (EHO), Garra Rufa optimization (GRO), particle swarm optimization (PSO), and genetic algorithm [6]. Another study by Victoire and Jeyakumar [7] reported the use of PSO to solve different forms of ED, including the two-area ED with tie line limits, ED of generators with forbidden operation zones, and ED with different fuel choices.…”
Section: Introductionmentioning
confidence: 99%